Diagnóstico del uso docente de las Tecnologías de la Información y Comunicación mediante el modelo SAMR en el nivel de educación general básica superior de la unidad educativa Pio Jaramillo Alvarado durante el año lectivo 2022-2023. - Merchán Infante, Pedro Vicente (2023)
Globalization and the communication society make it necessary to propose to the teaching staff an investigation with the aim of diagnosing the use of Information and Communication Technologies in teaching by using the SAMR model, under the deductive method, with a quantitative approach, exploratory-descriptive scope and transversal research design. Participants comprised 115 teachers from the State school and 21 teachers from the higher basic general education level. The indicator "Communicates and sends class materials to students by e-mail" was therefore found to be the most significant at the Substitution level. The indicator, Augmentation, corresponds to "Provides feedback to their students via email"; while the indicator, Modification, indicates that collaborative tools enhance self-learning; in the indicator, Redefinition, "Encourages their students to generate their own interactive content on platforms like Wordpress, Blogger, Tumblr, among others" stands out.; and finally, in the Use of educational resources indicator, it is worth mentioning "Individualized and instant monitoring of students' progress through platforms to create quizzes such as Kahoot, Socrative, Google Classroom, among others". Keywords: Use of ICT, teacher, SAMR Model, higher basic general education.